Literasi Keuangan dalam Pertimbangan Keputusan Investasi Tinjauan dari Gender - Gede Widiadnyana Pasek (Universitas Pendidikan Ganesha, 2022)
This study aims to determine the differences in investment decision attitudes between maler and female who are given financial literacy and those who are not given financial literacy. The number of participants in this experimental study was 85 participants. The design of this study was a 2 X 2 factorial design. After the experiment ended, the data were analyzed using a 2-way ANOVA statistical analysis. The results showed (1) there were differences in investment decision behavior between those who were given financial literacy and those who were not given financial literacy, (2) there were differences investment decisions between male gender and female gender Keywords: Financial Literacy, Invesment Decision, Gender